The detection of the urinary metabolites of 1‐[(5‐fluoropentyl)‐1H‐indol‐3‐yl]‐(2‐iodophenyl)methanone (AM‐694), a high affinity cannabimimetic, by gas chromatography – mass spectrometry. Issue 2 (23rd April 2012) - Grigoryev, Andrej; Kavanagh, Pierce; Melnik, Aleksandra
<x xml:space="preserve">Abstract</x> AM‐694 (1‐[(5‐fluoropentyl)‐1H‐indol‐3‐yl]‐(2‐iodophenyl)methanone), a synthetic indole‐based cannabimimetic, was first reported to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) via the Early Warning System (EWS) by Irish authorities in 2010. Using gas chromatography–mass spectrometry (GC‐MS), we have identified six AM‐694 metabolites in post‐ingestion samples. The metabolites were tentatively identified as products of (1) hydrolytic defluorination, (2) carboxylation, (3) monohydroxylation of N‐alkyl chain, and (4) hydrolytic defluorination combined with monohydroxylation of N‐alkyl chain. The parent compound was not detected. The excretion of major metabolites was observed up to 117 h following administration. One metabolite (a product of hydrolytic defluorination) was also identified in urine samples from two individuals admitted to hospital suffering from suspected drug overdoses. Copyright © 2012 John Wiley & Sons, Ltd.